CT and MR Imaging Findings of Periorbital Lipogranuloma Developing after Endoscopic Sinus Surgery - Yang, B.T.; Liu, Y.J.; Wang, Y.Z.; Wang, X.Y.; Wang, Z.C. (American Journal of Neuroradiology, 2012)
SUMMARY: Periorbital lipogranuloma is a rare complication after ESS and presently lacks specific imaging reports. The purpose of this study was to describe the CT and MR imaging features of periorbital lipogranuloma. We retrospectively reviewed 9 patients with histology-confirmed periorbital lipogranuloma. All 9 patients underwent CT and MR imaging. Five lipogranulomas were located in the right eyelid and 4 in the left eyelid, which extended into the extraconal space to some degree. The lesions displayed an irregular shape and had an ill-defined margin. Multiple, specked, or nodular foci containing fat were scattered within these lesions. The lesions demonstrated moderate heterogeneous contrast enhancement on contrast-enhanced MR imaging. The TICs showed a persistent pattern (type I) in 6 patients undergoing DCE MR imaging. Thus, an ill-defined, irregular-shaped periorbital mass with multiple foci containing fat, combined with an ESS history, can help to accurately diagnose this entity. DCEdynamic contrast-enhancedESSendoscopic sinus surgeryHUHounsfield unitsTICtime-intensity curveTpeaktime to peak enhancementWRwashout ratio